2005
DOI: 10.1002/ijc.20921
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an immunochemical fecal occult blood test with automated reading in screening for colorectal cancer in a general average‐risk population

Abstract: Colorectal cancer screening is a high public health priority in all industrialized countries. However, the low sensitivity of the common guaiac screening test (HemoccultII) makes practitioners and public health decision makers reluctant to set up a national screening program. In recent years, immunochemical tests based on the use of a specific antibody have been found to be more sensitive than the HemoccultII test. However, for screening purposes, any gain in sensitivity is of interest only if specificity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 16 publications
2
53
0
1
Order By: Relevance
“…Our previous studies have demonstrated that I-FOBT is preferable to G-FOBT from a public health point of view because the availability of quantitative Hb measurement offers the possibility to choose a positivity rate offering both high sensitivity and high specificity (Launoy et al, 2005;Guittet et al, 2007). This study suggests that I-FOBT is also preferable to G-FOBT from a clinical point of view, because it is capable of detecting good prognosis cancers of the rectum and high-risk adenomas that are missed by G-FOBT.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that I-FOBT is preferable to G-FOBT from a public health point of view because the availability of quantitative Hb measurement offers the possibility to choose a positivity rate offering both high sensitivity and high specificity (Launoy et al, 2005;Guittet et al, 2007). This study suggests that I-FOBT is also preferable to G-FOBT from a clinical point of view, because it is capable of detecting good prognosis cancers of the rectum and high-risk adenomas that are missed by G-FOBT.…”
Section: Discussionmentioning
confidence: 99%
“…Zappa et al (2001) used the proportional interval cancer incidence method, and reported 1-and 2-year sensitivity estimates for CRC for 1-day RPHA testing of 89 and 82%, respectively, whereas corresponding estimates for 3-day G-FOBT were 64 and 50%, respectively. Using the traditional method, Launoy et al (2005) reported a 2-year sensitivity estimate of 85% for a RPHA-derived test (Magstream) with a low-positivity cutoff and a recall rate of 6%.…”
Section: Sensitivity Of Latexmentioning
confidence: 99%
“…6,8 Reported sensitivities in these studies have ranged from 40.5% to 94%. 7,8,21 Our results are likely more reflective of the expectations for a community-based program. We report AUCs for colorectal carcinoma in subgroup analysis of 0.75 to 0.85, which are considerably lower than those reported by Tao et al, 22 who reported AUCs for the 3 quantitative tests of 0.90 to 0.92.…”
Section: Resultsmentioning
confidence: 61%
“…5 Recent research, however, has indicated that FIT is more sensitive than fecal occult blood tests as well as being more convenient for patients. [6][7][8][9][10] Fecal immunochemical testing also offers advantages to clinical laboratories, including the potential for automation, the ability to customize the cutoff level to define a positive test, and improved cost-effectiveness. [11][12][13][14][15][16] Finally, by eliminating patients who do not need a colonoscopy, a FIT screening program may be more cost-effective than colonoscopybased screening.…”
mentioning
confidence: 99%